INTERNAL CONSISTENCY OF THE INTERNATIONAL PHYSICAL ACTIVITY QUESTIONNAIRE (SHORT VERSION) FOR USE IN RESEARCH WITH BRAZILIAN UNIVERSITY STUDENTS - Sousa, Thiago Ferreira de (2024)
The objective of this study was to analyze the psychometric quality regarding the level of internal consistency of the International Physical Activity Questionnaire (IPAQ), short version, in Brazilian university students. This is a cross-sectional study whose data collection was carried out via questionnaire at a public university in the state of Minas Gerais, Brazil. Physical activities were analyzed, considering the minutes spent walking, moderate and vigorous intensity. Descriptive analyses, Pearson correlation and internal consistency were used using the MacDonald’s Omega test (MO) and Conbrach’s alpha (α). All analyzes were carried out stratified by sex using SPSS software, version 25.0. 309 men and 565 women participated in the study. The internal consistency levels among men were MO of 0.670 and α of 0.469, among women they were OM of 0.580 and α of 0.480. There were significant correlations between physical activity variables, with the exception of walking time and vigorous intensity among men. It is concluded that the IPAQ, short version, analyzed in three variables (walking, moderate and vigorous) relating to minutes of practice, showed low internal consistency in Brazilian university students.